Critical analysis of the definitions of reservoir and carrier in epidemiology - Sara Maribel Ramírez-Ozuna; Gregorio Presentado-Prantte; Vicente Luis Acuña-Caballero (Journal of the Selva Andina Animal Science)
Most authors, in articles and texts on epidemiology, differ in certain terms in the definitions of carrier and reservoir, so it is interesting to analyze them in order not to fall into confusions that lead to a misunderstanding, and therefore in their responsibility in the epidemiology of the disease, since the reservoir can easily be confused conceptually with the carrier, being very different in origin, considering also that the sanitary measures aimed at combating the disease are based on these concepts.